2018
DOI: 10.1186/s12884-018-1773-6
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of barriers and facilitators of dental service utilization of pregnant women: A triangulation approach

Abstract: BackgroundPregnant women are vulnerable to a wide range of oral health conditions that could be harmful to their own health and future child. Despite the usefulness of regular dental service utilization in prevention and early detection of oral diseases, it is notably low among pregnant women. In this qualitative study, we aimed to explore barriers and facilitators influencing pregnant women’s dental service utilization.MethodsUsing a triangulation approach, we included pregnant women (n = 22) from two public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 33 publications
9
58
1
11
Order By: Relevance
“…A survey among 625 women (a predominantly Caucasian population of relatively high socioeconomic status) living in Johnson County, Iowa, revealed that increased prenatal dental visits were associated with being married, having more frequent dentist visits when not pregnant, having dental insurance, and knowledge of the possible connection between oral health and pregnancy outcomes [13]. Similar effects have been reported globally: Australian [14,15] and Iranian pregnant women [16] reported that the barriers to utilization of prenatal dental care utilization included lack of knowledge, false beliefs, cost, fear, the limited number of dentists providing care to pregnant women, and inadequate recommendations from health professionals.…”
Section: Introductionmentioning
confidence: 80%
“…A survey among 625 women (a predominantly Caucasian population of relatively high socioeconomic status) living in Johnson County, Iowa, revealed that increased prenatal dental visits were associated with being married, having more frequent dentist visits when not pregnant, having dental insurance, and knowledge of the possible connection between oral health and pregnancy outcomes [13]. Similar effects have been reported globally: Australian [14,15] and Iranian pregnant women [16] reported that the barriers to utilization of prenatal dental care utilization included lack of knowledge, false beliefs, cost, fear, the limited number of dentists providing care to pregnant women, and inadequate recommendations from health professionals.…”
Section: Introductionmentioning
confidence: 80%
“…A survey among 625 women (a predominantly Caucasian population of relatively high socioeconomic status) living in Johnson County, Iowa, revealed that increased prenatal dental visits were associated with being married, having more frequent dentist visits when not pregnant, having dental insurance, and knowledge of the possible connection between oral health and pregnancy outcomes [14]. Similar effects have been reported globally: Australian [15,16] and Iranian pregnant women [17] reported that the barriers to utilization of prenatal dental care utilization included lack of knowledge, false beliefs, cost, fear, the limited number of dentists providing care to pregnant women, and inadequate recommendations from health professionals.…”
Section: Introductionmentioning
confidence: 80%
“…Ferramentas como esta são muito importantes para ampliar o conhecimento dos profissionais envolvidos nos serviços e, consequentemente, dos próprios pacientes (Lee & Moon, 2016). Ainda, considerando a baixa adesão das gestantes ao pré-natal odontológico (Bahramian, Mohebbi, Khami & Quinorez., 2018;George et al, 2018), torna-se fundamental o trabalho integrado entre os profissionais envolvidos com o pré-natal, no intuito de que eles através de um conhecimento ampliado sobre o tema, também possam incentivar as gestantes a aderir ao acompanhamento odontológico durante a gestação, considerando a sua importância para o bem estar da mãe e do bebê.…”
Section: Discussionunclassified